SARS-CoV-2 neutralizing camelid heavy-chain-only antibodies as powerful tools for diagnostic and therapeutic applications - Schlör, Anja; Hirschberg, Stefan; Amor, Ghada Ben; Meister, Toni Luise; Arora, Prerna; Pöhlmann, Stefan; Hoffmann, Markus; Pfaender, Stephanie; Eddin, Omar Kamal; Kamhieh-Milz, Julian; Hanack, Katja (Frontiers in Immunology, 2022)
Introduction The ongoing COVID-19 pandemic situation caused by SARS-CoV-2 and variants of concern such as B.1.617.2 (Delta) and recently, B.1.1.529 (Omicron) is posing multiple challenges to humanity. The rapid evolution of the virus requires the adaptation of diagnostic and therapeutic applications. Objectives In this study, we describe camelid heavy-chain-only antibodies (hcAb) as useful for novel in vitro diagnostic assays and for therapeutic applications due to their neutralizing capacity. Methods Five antibody candidates were selected out of a naïve camelid library by phage display and expressed as full-length IgG2 antibodies. The antibodies were characterized by Western blot, enzyme-linked immunosorbent assays, surface plasmon resonance with regard to their specificity to the recombinant SARS-CoV-2 Spike protein, and to SARS-CoV-2 virus-like particles. Neutralization assays were performed with authentic SARS-CoV-2 and pseudotyped viruses (wildtype and Omicron). Results All antibodies efficiently detect recombinant SARS-CoV-2 Spike protein and SARS-CoV-2 virus-like particles in different ELISA setups. The best combination was shown with hcAb B10 as catcher antibody and HRP-conjugated hcAb A7.2 as the detection antibody. Further, four out of five antibodies potently neutralized authentic wildtype SARS-CoV-2 and particles pseudotyped with the SARS-CoV-2 Spike proteins of the wildtype and Omicron variant, sublineage BA.1 at concentrations between 0.1 and 0.35 ng/mL (ND50). Conclusion Collectively, we report novel camelid hcAbs suitable for diagnostics and potential therapy.